Hardware Implementation of 3-level Inverter using Microcontroller for Single Phase Induction Motor - Veena B.M.; Parimala S.K. (International Journal of Reconfigurable and Embedded Systems (IJRES), 2016)
The conventional two level inverter has many limitations for high voltage & high power applications. The term multilevel began with the three-level inverter. Subsequently, several multilevel inverter topologies have been developed. However, the elementary concept of a multilevel inverter to achieve higher power is to use a series of power semiconductor switches with several lower voltage dc sources to perform the power conversion by synthesizing a staircase voltage waveform. Output voltage of 3 level inverter consists of 3 levels, which results smoother output. And hence the THD will be reduced. In this paper Simulink of 3 level inverter and the hardware implementation of micro controller based control of multilevel inverter for single phase Induction motor are presented.